Assessment of Water Quality of Kolpu Khola in Sisdol Landfill Area of Nuwakot District - Shrestha, Ujjwal Thapa; Shrestha, Jaya K.; Devkota, Rohini P. (Nepal Journal of Science and Technology, 2015)
The present study was carried out to determine the impact of the leachate contamination on water quality of Kolpu Khola nearby Sisdol landfill site. Water samples were collected from six different sites of Kolpu Khola from upstream to downstream. The samples were collected in clean plastic bottles from a leachate collection from December, 2007 to August, 2008 and analyzed for the determination of physical parameters (pH, conductivity, temperature) and chemical parameters (dissolved oxygen, alkalinity, chloride, calcium hardness, total hardness, BOD5, PO4-P, NO3-N, NH4-N) using a standard method. It was found that leachate was severely polluted with most of the physicochemical parameters being higher than the generic standard for industrial effluent discharged into inland surface water. The variation of BOD and COD showed that the chemistry of the leachate in the landfill was undergoing rapid change. The surface water of Kolpu Khola was not polluted from chloride point of view and the spatial variation of chloride content was significant at 0.01 significance level. The river water at all the sites under study had PO4-P above natural range i.e. 0.005 to 0.020 mg/l and was not suitable for livestock drinking and for aquatic animals with reference to most of the physicochemical parameters studied. DOI: http://dx.doi.org/10.3126/njst.v15i1.12026 Nepal Journal of Science and Technology Vol. 15, No.1 (2014) 107-114